The attenuation performance of locally resonant acoustic metamaterials based on generalised viscoelastic modelling. (November 2017) - Lewińska, M.A.; Kouznetsova, V.G.; van Dommelen, J.A.W.; Krushynska, A.O.; Geers, M.G.D.
Abstract: Acoustic metamaterials are known as a promising class of materials interacting with acoustic and/or elastic waves. Band gap formation is one of the most spectacular phenomena that they exhibit. Different ways to broaden the attenuated frequency ranges are still being actively explored. It turns out that material damping through intrinsic viscoelastic material behaviour, if accurately tailored, may contribute to the enhancement of the performance of a properly designed acoustic metamaterial. In this study, a locally resonant acoustic metamaterial with periodic multicoated inclusions with viscoelastic layers is investigated. Multiple attenuation regimes obtained with the considered geometry are joined for a certain level of viscosity of the coating layer. The analysis is performed using a generalised Maxwell model, which allows for an accurate description of nonlinear frequency dependent elastic properties, and thus is widely used to model the behaviour of many polymeric materials in a realistic way. The study reveals that variation of the material parameters of the rubber coating with respect to frequency influences not only the position of the band gaps but also the effectiveness of the wave attenuation in the frequency ranges around the band gaps.